Comparison of Microbial Community and Metabolites in Four Stomach Compartments of Myostatin-Gene-Edited and Non-edited Cattle - Zhou, Xinyu; Gu, Mingjuan; Zhu, Lin; Wu, Di; Yang, Miaomiao; Gao, Yajie; Wang, Xueqiao; Bai, Chunling; Wei, Zhuying; Yang, Lei; Li, Guangpeng (Frontiers in Microbiology, 2022)
Myostatin (MSTN), a major negative regulator of skeletal muscle mass and an endocrine factor, can regulate the metabolism of various organisms. Inhibition of the MSTN gene can improve meat production from livestock. Rumen microorganisms are associated with production and health traits of cattle, but changes in the microbial composition and metabolome in the four stomach compartments of MSTN-gene-edited cattle have not previously been studied. Our results indicated that microbial diversity and dominant bacteria in the four stomach compartments were very similar between MSTN-gene-edited and WT cattle. The microbiota composition was significantly different between MSTN-gene-edited and WT cattle. Our results shown that the relative abundance of the phylum Proteobacteria in the reticulum of MSTN-gene-edited cattle was lower than that of WT cattle, while the relative abundance of the genus Prevotella in the omasum of MSTN-gene-edited cattle was significantly higher than that of WT cattle. Metabolomics analysis revealed that the intensity of L-proline and acetic acid were significantly different in the rumen, reticulum, and abomasum between the two types of cattle. Meanwhile, pathway topology analysis indicated that the differential metabolites were predominantly involved in arginine biosynthesis and glutamate metabolism in the rumen, reticulum, and omasum, but were mainly involved in pyruvate metabolism and glycolysis/gluconeogenesis in the abomasum. Spearman correlation network analysis further demonstrated that there was a significant correlation between microflora composition and metabolic pathways. These finding provide clues for studying nutrient digestion and absorption ability of MSTN-gene-edited cattle.